Vórtices BPS no modelo de Maxwell- CP(2) com estrutura interna - ANDRADE, João Luís Brandão (2019)
In this dissertation, I present the original BPS vortices (Bogomol'nyi-Prasad-Sommer)eld) inherent in a gauge model Maxwell-CP(2) from the general scenario CP (N-1) (in which N = 3, with N corresponding to the number of components of the CP (2) field), when subjected to the presence of an additional, real and neutral scalar field. Then, focusing on radially symmetrical structures, we construct a first-order structure for the model, using the Bogomol'nyi procedure. From the minimization of the total energy, we obtain general expressions for the minimum energy of the model, whose value has an extra contribution due to the presence of the neutral field, and for the respective first order equations (BPS equations), in which both the minimum energy while the BPS equations depend directly on the functional structure of the dielectric function. The introduction of the scalar field, which interacts with the electromagnetic sector via an unusual dielectric function, produces significant modifications in the shape of the resulting BPS vortices, such changes being understood as the manifestation of internal structures originated by the presence of the additional neutral field.